PELATIHAN EKONOMI SYARIAH BAGI GURU SMK SEBAGAI INISIASI PEMBUKAAN PROGRAM STUDI PERBANKAN SYARIAH - Hasan Mukhibad; Prabowo Yudo Jayanto (Universitas Islam kalimantan MAB, 2017)
The development of Islamic banking industry is rapid. Data from Indonesian Bank shows the growth of asset annually (YoY) are 33.49%. This rapid growth brings the consequences of increasingly needed of Human Resources who understand the concept, practical and operationalization of Islamic bank. Nevertheless, the results of Indonesian's Bank research showing that there are 90% of Islamic bank employees do not has Islamic economic background. To meet the needs of this human resources, some vocational high schools (Sekolah Menengah Kejuruan) already has expertise program in Islamic bank. However, the Collage of Education in Indonesia does not yet has a department of Islamic Economic Education or a similar study program that produces a teacher of Islamic bank. Synergy between collage and teachers is needed to increase the teachers competence in teaching in Islamic Bank. This community service program done to improve understanding of teachers by conducting training in Demak District. Training materials related to the concept of Islamic economy, operationalization of Islamic banks and accounting. Based on data using a different test T-Test yielded a significance value are 0.000. This result that this training provides benefits of improving teachers' understanding of Islamic economy.